The understanding of the role of education as a mechanism for capacity building among nomadic Fulani communities in Kaduna, Nigeria - Dahiru, Suleiman (2017)
In recent time, it is evident that the number of uncounted out-of-school children from nomadic pastoralist groups has quite increased globally, even though much effort have been made by government and agencies for long to educate them, but have not achieved as expected. These have left them at the mercy of being isolated, illiterate, ignorant, attain low educational achievement and underdeveloped. However, it was from this background, the study seeks to explore how nomadic Fulani communities in Kaduna understand the importance of education as a mechanism for building capacity in Kaduna. Methodologically, a qualitative method was employed and a case study design was used in this study. Whereas, purposive sampling was used to identify ten participants from the categories of Fulani parents as unit of analysis, one nomadic teacher and one nomadic education officer were purposively located based on a criterion set. The face to face interviews was used for data collection. Thus, the interview data was transcribed, coded and analysed inductively. Thematically, two themes were inductively derived as the main findings, firstly that nomadic Fulani understand education as a process for capacity building. This include both at the level of the individual and community capacity building. Secondly, cultural believe and social factors such as lack of role model, parent ignorance of the importance of the formal education, and the fear of fragmentation of the social capital were found as the main aggravating cause of the Fulani nomadic poor perception and decline in participation in the formal education for capacity building. It is from these findings that the researcher concluded that the nomadic Fulani in spite their dropout from the education system still believe that education is a capacity building process that can empowered the pastoralist to achieved community development, but the education system should concur to the moral cultural value (pulaaku) which is believed to be the identity of the group. These findings can be of significance to policymakers, government, agencies, and community developers in the design and execution of educational programmes or project for such marginalised community to achieve acceptability, participation and sustainability.